An Epoxy Adhesive Crosslinked through Radical‐Induced Cationic Frontal Polymerization. Issue 12 (5th September 2021) - Turani, Matteo; Baggio, Andrea; Casalegno, Valentina; Salvo, Milena; Sangermano, Marco
Abstract: UV‐initiated cationic frontal polymerization is exploited as a solvent‐free, extremely fast, and low‐temperature technique to obtain epoxy‐based adhesives. Epoxy formulations are prepared by blending commercial resins at different weight ratios and adding photo and thermal initiators at different percentages. In addition, the influence of other critical parameters, including the joint thickness, the nature of the adherends, and the temperature, is studied. As the reaction front is thermally sustained, the boundary conditions play a key role during the curing process and heat dissipation through the adherends in particular. The thermal properties of the epoxy formulation are studied through differential scanning calorimetry analysis, and the joint strengths are investigated by carrying out single lap off‐set shear tests under compression. The results demonstrate the feasibility of obtaining joints by means of the radical induced cationic frontal polymerization of the epoxy adhesives, which exhibit comparable epoxy group conversion and mechanical performances to the ones cured by traditional energy‐intensive techniques. Abstract : UV‐initiated cationic frontal polymerization is exploited as a solvent‐free, extremely fast, and low‐temperature technique to obtain epoxy‐based adhesives. The results demonstrate the feasibility of obtaining joints which exhibit comparable epoxy group conversion and mechanical performances to the ones cured by traditional energy‐intensive techniques.